Study for the Adaptation of a Rapid Assessment Protocol for Lentic Environments in Presidente Prudente (São Paulo/Brazil) - Ziliotto, Beatriz Garcia; Romero, Danielli Cristina Granado (Journal of Technology and Sustainable Management, 2024)
Amid the context of urban transformation that extends from the earliest settlements along the banks of rivers and streams to the present day, it is evident that in the process of urban planning and occupation, these water bodies were often perceived as barriers that limited and shaped the urban layout. The objective of this study was to develop a study for the adaptation of a rapid assessment protocol focused on lentic environments in Presidente Prudente, São Paulo. This study fills a theoretical gap by addressing the lack of specific adaptations for lentic environment assessment protocols. The research was conducted through literature reviews comparing the characteristics of lentic and lotic environments, and the results revealed that lentic environments exhibit several characteristics that differentiate them from lotic environments, highlighting the need for continuous adaptations in the assessment protocol. This analysis not only contributes to academic knowledge but also points to the need for more effective and sustainable management practices concerning these ecosystems.